807 Outcomes of Endovascular Embolization for Vein of Galen Malformations: An Individual Participant Data Meta-Analysis. (April 2023) - Hale, Andrew T.; Savage, Cody; Parr, Matthew Saifi; Hedaya, Alexander; Saccomano, Benjamin; Tsema, Georges Bouobda; Hafeez, Muhammad; Tanweer, Omar; Kan, Peter; Solomon, Laurent; Deloison, Benjamin; Meila, Dan; et al.
Abstract : INTRODUCTION: Understanding outcomes of Vein of Galen malformation (VOGM) embolization have been limited by small sample size and heterogeneity of reported series. METHODS: We performed a systematic review and individual patient data meta-analysis of VOGM endovascular outcomes according to PRISMA guidelines. Individual patient data (IPD) including demographic, intra/post-operative complications, treatment efficacy (partial or complete occlusion), and neurological outcome were collected. Mixed-effects logistic regression with random effects modeling and Bonferroni correction was used (p<0.003 threshold for statistical significance). The primary and secondary outcomes were all-cause mortality and poor clinical outcome (moderate/severe developmental delay or permanent disabling injury), respectively. RESULTS: Thirty-five studies totaling 307 patients evaluating outcomes of endovascular embolization for VOGM were included. Mean follow up was 42 (±57) months. Our analysis contained 42% neonates (<1 month) at first embolization, 45% infants (1 month < 2 years), and 13% children (>2 years). Complete occlusion was obtained in 48% of patients. Overall all-cause mortality was 16%. Overall, good clinical outcome was achieved in 68% of patients. First embolization as a neonate (OR = 6.93 [1.99-24.08] p<0.001) and incomplete occlusion (OR = 10.87 [1.86-63.55], p < 0.001) were associated with mortality. First embolization as a neonate (OR = 3.24 [1.47-7.15], p < 0.001), incomplete occlusion (OR = 5.26 [2.06-13.43], p < 0.001), and heart failure at presentation (OR = 3.10 [1.03-9.33], p = 0.002) were associated with poor clinical outcomes. Sex, angioarchitecture of lesion, embolization technique, and single or multistage embolization were not associated with mortality or clinical outcome. CONCLUSIONS: For the first time, we identify incomplete embolization treatment associated with poor clinical outcome and mortality. While this study provides the highest level of evidence for VOGM embolization to date, prospective multicenter studies are needed to understand the optimal treatment strategies, outcomes, and natural history after VOGM embolization.